Mountain & Alpine Medicine - Tannheimer M; 2 (Dynamic Media Sales Verlag, 2020)
Accidents during mountaineering are special because mountain rescue operations are time-consuming and material-intensive. Since even in Europe it takes a long time for professional help to reach the injured person, first aid rugulary has to be provided by the accompanying mountaineers. This case report of a seriously injured person at an altitude of 5,700 m describes the special challenges of such a rescue operation.After the accident, the patient has to be moved out of the immediate danger zone to enable examination, treatment must be startet and further transport organized. This requires profound training in makeshift mountain rescue techniques, the use of diagnostic algorithms and safe application of medications.Generally, material and manpower are very limited in such situations and exhaustion due to the challenging tour is an aggravating factor. Therefore, the group has to look for external help and support at an early stage. For this purpose, efficient communication equipment is required and contacts must already be established. There is a high level of emotional stress when treating friends. In order to cope successfully with such a stressful situation, profound education and intensive training, as well as a strategy for external support developed in advance, are necessary.Key Words: Mountain Rescue, Traumatic Brain Injury, S-Ketamine, Remote Area, Wilderness Medicine